Structure of the EF-hand domain of polycystin-2 suggests a mechanism for Ca²⁺-dependent regulation of polycystin-2 channel activity - Petri, Edward T; Ćelić, Andjelka; Kennedy, Scott D; Ehrlich, Barbara E; Boggon, Titus J; Hodsdon, Michael E (Proceedings of the National Academy of Sciences - PNAS, 2010)
The C-terminal cytoplasmic tail of polycystin-2 (PC2/TRPP2), a Ca²⁺-permeable channel, is frequently mutated or truncated in autosomal dominant polycystic kidney disease. We have previously shown that this tail consists of three functional regions: an EF-hand domain (PC2-EF, 720-797), a flexible linker (798-827), and an oligomeric coiled coil domain (828-895). We found that PC2-EF binds Ca²⁺ at a single site and undergoes Ca²⁺-dependent conformational changes, suggesting it is an essential element of Ca²⁺-sensitive regulation of PC2 activity. Here we describe the NMR structure and dynamics of Ca²⁺-bound PC2-EF. Human PC2-EF contains a divergent non-Ca²⁺-binding helix-loop-helix (HLH) motif packed against a canonical Ca²⁺-binding EF-hand motif. This HLH motif may have evolved from a canonical EF-hand found in invertebrate PC2 homologs. Temperature-dependent steady-state NOE experiments and NMR R₁ and R₂ relaxation rates correlate with increased molecular motion in the EF-hand, possibly due to exchange between apo and Ca²⁺-bound states, consistent with a role for PC2-EF as a Ca²⁺-sensitive regulator. Structure-based sequence conservation analysis reveals a conserved hydrophobic surface in the same region, which may mediate Ca²⁺-dependent protein interactions. We propose that Ca²⁺-sensing by PC2-EF is responsible for the cooperative nature of PC2 channel activation and inhibition. Based on our results, we present a mechanism of regulation of the Ca²⁺ dependence of PC2 channel activity by PC2-EF.